High-pressure high-temperature synthesis and characterization of B10C - Seth Iwan; Kallol Chakrabarty; Paul A. Baker; Yogesh K. Vohra (AIP Advances, 2024)
The boron-rich boron carbide materials have been traditionally synthesized by adding boron powder to B4C material and subjecting it to hot pressing sintering for materials composition containing 8.8–20 at. % carbon in boron (composition range of B10.4C to B4C). Our study explores a synthesis route for B10C starting from high-purity boron and carbon and direct conversion under high pressure and high temperature (HPHT) conditions of 2000 °C and 6–8 GPa. Synthesis was verified via x-ray diffraction analysis, showing the conversion of the high-purity boron and carbon powder mixture into a hexagonal B10C structure (R-3m space group) with lattice parameters of a = b = 5.6115 Å and c = 12.197 Å. The concentration of boron was measured through x-ray photoelectron spectroscopy, confirming the B10C ratio. The measured nanoindentation mean hardness of B10C was 40 GPa. Raman spectroscopy of the HPHT synthesized sample shows characteristic vibrational breathing modes of boron icosahedron and an additional intense band at a vibrational frequency of 380 cm−1. This Raman band, which appears notably weaker in earlier studies and B4C samples, is assigned to the linear chain of B–B–B and attributed to the maximal incorporation of boron within the hexagonal structure.